Nine professional conversations to change our schools : a dashboard of options - Sommers, William A.; Zimmerman, Diane P. (Corwin, 2018)
Improve collective efficacy in schools through meaningful professional conversations In a landscape where technology can undermine personal connections, even the most talented educator can feel like they're practicing their craft in isolation. Nine Professional Conversations to Change Our Schools is a framework for revitalizing the art of the professional conversation. It guides educators through structures for collaboration, grants access to vast storehouses of applied wisdom, and facilitates a consensual knowledge base for standards of excellence. 9 conversational strategies designed to.